Formulation of Customary Criminal Law in Future Criminal Code and Legal Enforcement in Indonesia - Rusdi Antara, Gede Eka; Budiana, I Nyoman; Sadnyini, Ida Ayu (Susbtantive Justice International Journal of Law, 2021)
The pros and cons were debated in limiting national legal substance with full recognition of Customary Criminal Law in the bill of Criminal Code and its future enforcement. On the other hand, there are arguments against the inclusion of Customary Criminal Law in the Criminal Code and the resulting disparities in legal enforcement caused by some Judges’ ignorance of judging customary criminal cases settled with the imposition of customary sanctions, which resulted in an unjust situation. This article aims to serve as a legal academic framework for establishing, identifying, and analyzing the formulation of Customary Criminal Law into the Indonesian Criminal Code, as well as to contribute to the discussion of judges’ roles in sentencing customary criminal cases, which they should determine and judge based on customary law. This article demonstrated the use of normative legal research in conjunction with statutory law, legal conceptual, and philosophical approaches to law. This article discovered that: first, several issues concerning the formulation of Customary Criminal Law into several national Bills of Criminal Code were debatable; second, it also cannot be enacted due to conflicting contexts with Criminal Law principles, unwillingness, and an ambiguous law-making process. Furthermore, the prospect of including the Customary Criminal Law in the Bill of Criminal Code is based on various justifications and legal needs that reflect the diverse local genius that still exists and adheres to Pancasila law principles. Additionally, it relates to a proposed new paradigm that Judges and other legal enforcers should adopt when enforcing Customary Criminal Law in any criminal customary case.